2021
DOI: 10.1111/jan.15023
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in cancer patients with different preferences for nurse spiritual therapeutics: The role of psychological capital

Abstract: Quality of life (QoL) is considered as an individual's subjective perception of his/her position in society, which is an important issue for patients with cancer (Valdez & Brennan, 2018). Studies indicate that because of clinical manifestations of cancer, a set round of treatment, physical dysfunction and socio-economic pressures, cancer patients experienced low levels of QoL (Konieczny et al., 2020;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…PsyCap has been proven to be effective in improving individual performance and relieving negative emotions. Empirical research showed that PsyCap was negatively associated with psychological symptoms, such as anxiety ( Minglu et al, 2020 ) and depression ( Shen et al, 2014 ), and could improve nurses’ care competencies ( Guo et al, 2021 ) and quality of life of cancer patients ( Guo et al, 2022 ). And PsyCap also played a mediating role in the relationship between anxiety or depression and other related variables ( Rahimnia et al, 2013 ; Jiang, 2021 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…PsyCap has been proven to be effective in improving individual performance and relieving negative emotions. Empirical research showed that PsyCap was negatively associated with psychological symptoms, such as anxiety ( Minglu et al, 2020 ) and depression ( Shen et al, 2014 ), and could improve nurses’ care competencies ( Guo et al, 2021 ) and quality of life of cancer patients ( Guo et al, 2022 ). And PsyCap also played a mediating role in the relationship between anxiety or depression and other related variables ( Rahimnia et al, 2013 ; Jiang, 2021 ; Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As for the term ‘spirituality’, which is unfamiliar to many Chinese, the phrase ‘writing about my spirituality’ was modified to ‘writing down the spiritual world in my brain’, and specific examples of spiritual resources such as ‘temple’, ‘church’ or ‘other religious sites’ were added (Guo et al, 2022; Li et al, 2017; Xie et al, 2019). Items/questions that were determined to be detrimental to construct validity, based on the results of validity testing/factor analysis, were deleted (Chang et al, 2022; Cheng et al, 2018; Du et al, 2022; Guo et al, 2022; Li et al, 2017; Lin et al, 2015; Tao et al, 2022; Xie et al, 2019; Zhao et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐six studies were quantitative designs and were conducted in mainland China ( n = 18), Taiwan ( n = 6), and the USA ( n = 2). Among them, five studies explored spiritual needs (Cheng et al, 2018; Deng et al, 2015; Du et al, 2022), spiritual state (Cheng et al, 2019), and spiritual nursing needs (Li et al, 2017); 11 studies examined the correlation between spiritual aspects and other variables (Chang et al, 2022; Cho & Lu, 2017; Feng et al, 2021; Guo et al, 2022; Kao et al, 2013; Li et al, 2012, 2022; Tao et al, 2022; Wang & Lin, 2016; Yang et al, 2021; Yeung et al, 2014); seven studies were conducted to translate spirituality‐related instruments originally developed in Western countries into Chinese for use with Chinese people with cancer (Astrow et al, 2012; Lin et al, 2015; Liu et al, 2016; Lo et al, 2016; Tang & Kao, 2017; Xie et al, 2019; Zhao et al, 2019); and three studies aimed to examine the effects of interventions on the spirituality of Chinese people with cancer (Chen et al, 2021; Sun et al, 2021; Xiao et al, 2022). One study with a mixed methods design was conducted in mainland China to explore the quality of life (including a spiritual dimension) of breast cancer survivors (Cheng et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations